The Kirkbride buildings in contemporary culture (1850–2015): from 'moral management' to horror films. Issue 3 (September 2019) - Pérez-Fernández, Francisco; López-Muñoz, Francisco
The so-called 'Kirkbride Plan' is a type of mental institution designed by the American psychiatrist Thomas Story Kirkbride. The Kirkbride-design asylums were built from 1848 to the end of the nineteenth century. Their structural characteristics were subordinated to a certain approach to moral management: exposure to natural light, beautiful views and good air circulation. These hospitals used several architectural styles, but they all had a similar general plan. The popularity of the model decreased for theoretical and economic reasons, so many were demolished or reused, but at least 25 of the original buildings became protected places. Over the years, surrounded by a legendary aura, these buildings have become a leitmotif of contemporary popular culture: 'the asylum of terror'.